Modification of physicochemical properties and degradation of barley flour upon enzymatic extrusion. (February 2022) - Zhao, Shuna; Jiao, Aiquan; Yang, Yueyue; Liu, Qing; Wu, Wenqi; Jin, Zhengyu
Abstract: In order to evaluate the application potential of enzyme-extruded barley flour (EEBF) in the brewing of whole-barley beer, the physicochemical properties, mashing and fermentation effects of EEBF were studied, and conventional extruded barley flour (CEBF) and steam-cooked barley flour (SCBF) were taken as controls. The water solubility index (WSI) of EEBF (46.88%–52.63%) was much higher than that of CEBF (6.70%) and SCBF (4.59%). The results of degree of gelatinization (DG) and enthalpy (ΔH) suggested that EEBF was almost completely gelatinized, and the rapid visco analyzer (RVA) exhibited that the peak viscosity of EEBF was drastically reduced. The weight-average molecular weight of EEBF (<10 6  g/mol) was significantly lower than that of CEBF and SCBF. Scanning electron microscopy (SEM) showed that the heat-treatments caused starch granules to break and aggregate, and there were many hydrolyzed pores on the surface of EEBF. Both the long- and short-range order of EEBF were destroyed. Although EEBF caused serious filtration blocking, it greatly improved the alcohol content of finished beer (5.41%vol). Overall, the thermal modification of barley flour by enzyme-extrusion meets the needs of fermentation, and could improve the problem of limited leaching of unmalted barley, which was benefit for the production of whole-barley beer.